Government Policies and Their Impact on Youth Entrepreneurship: A Comparative Study of Kerala and Tamil Nadu - A P , Sajeev Kumar; Shanmugam , Dr. N; N , Dr. Madhusoodanan Kartha (International Journal of Accounting and Economics Studies, 2025)
This study examines the diverse impacts of government policies on youth-led entrepreneurship in the states of Kerala and Tamil Nadu. Drawing from coverage documents, youth surveys, and entrepreneurial overall performance statistics from 2015 to 2024, the comparative evaluation identifies critical differences in incubation aid, financial access, regulatory frameworks, and training projects. Kerala reveals a more potent public entrepreneurship infrastructure and mentorship programs, while Tamil Nadu emphasises financial incentives and business integration. The findings show that even as both states boost youth' entrepreneurial interest, Kerala's ecosystem yields more sustainable and growth-oriented ventures, while Tamil Nadu fosters a higher startup rate. Policy implications encompass a balanced integration of institutional guidance, focused financing, regulatory simplification, and talent development tailored to the demographics of young people. The examination contributes to the discourse on subnational entrepreneurship policy and informs country-level strategic planning.
Keywords: Youth entrepreneurship; Government policy; Kerala; Tamil Nadu; Comparative analysis; Incubation; Financial support